Mass atrocity, ordinary evil, and Hannah Arendt criminal consciousness in Argentina's Dirty War - Osiel, Mark (Yale University Press, 2001)
This text addresses Hannah Arendt's controversial argument that perpetrators of mass crimes are unaware of their wrong-doing, and therefore criminal laws do not adequately address these defendants. It applies Arendt's arguments to the perpetrators of mass crime in Argentina's Dirty War.